IMPLEMENTASI KURIKULUM 2013 MATA PELAJARAN PENJASORKES DI SEKOLAH PENGEMBANGAN DAN PERCONTOHAN - Yan Sonyardhi P; Anirotul Qoriah (Universitas Negeri Semarang, 2016)
This research aims to understand the implementation of curriculum 2013 on subject Penjasorkes in SMA Negeri 1 Batang and SMA Negeri 2 Batang 2014/ 2015. This research uses a qualitative approach that gives description about actual facts in the field work. The result of this research shows that based on qualitative descriptive analysis, 2 schools have operated the duty and capacity as the developing and sequential school quite well. Target of this research is the implementation of curriculum 2013, school's promptness, learning support, and responses of executants in school. Some findings of this research are teachers and students have not received comprehensive handbook of curriculum 2013 from Kemendikbud. Teachers both in SMA Negeri 1 Batang and SMA Negeri 2 Batang have received sample of syllabus and valid RPP from Kemendikbud. The implementation of scientific learning is still having problem; students seem to be less confident to show their ability in sports to their friends, sometimes teachers cannot move on from KTSP while learning process is happening, too many aspects for teachers processing the score, and the extension hour worsens them who have exercise class in the afternoon.